Effects of proprioceptive neuromuscular facilitation on the functional independence measure in patients with Parkinson’s disease. - Carvalho, Emilton Lima de; Queiroz, Ilkiane Pinheiro; Queiroz, Ilkilene Pinheiro; Batista, Ingred Merllin de Souza; Maciel, Thiago dos Santos; Arêas, Fernando Zanela da Silva (Manual Therapy, Posturology & Rehabilitation Journal, 2015)
Background: Parkinson’s disease is classified as a chronic, degenerative disease and is characterized by a regression in the number of dopaminergic neurons in the substantia nigra region, the main clinical features of PD are: muscle rigidity and tremor at rest six cycles per second. Objective: To evaluate the effects of pop on the Functional Independence Measure (FIM) in patient carriers of Parkinson disease. Method: The above study five elderly patients with Parkinson’s disease with a mean age of 82,5±10,33 years. The study was carried out applying the FIM questionnaire before and after treatment with PNF to assess cognitive and motor control levels. The patients were submitted to 10 sessions estimated time between 40 and 50 minutes. Results: The analysis of the functional independence of patients, although the results have been optimistic, improving patient’s functional pattern not observed statistically significant difference (p >0,05). Conclusion: It did not get positive results when assessing the level of motor and cognitive functional independence. Although there have been reports of improvement in locomotion and sphincter control by the patients themselves.